2003
DOI: 10.1007/s00244-002-2100-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contaminants in Liver and Kidney of Free-Ranging Northern Goshawks ( Accipiter gentilis ) from Three Regions of Germany

Abstract: The northern goshawk (Accipiter gentilis) is a top predator in the terrestrial food web of large parts of the Holarctic. Due to its sedentary nature and well-investigated feeding ecology, it represents the most suitable bird of prey species in continental Europe for monitoring environmental pollutants. We analyzed the levels of organochlorine pesticides, polychlorinated biphenyls (PCB), and nonessential heavy metals in organ samples of 62 free-ranging northern goshawks found dead or injured in Germany from 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…On the other hand, Kenntner et al (2003) did not observe such intersex relationships concerning mercury renal concentrations for German Goshawks, even though they recorded higher lead concentrations in the kidneys of females in comparison to males. That result may indicate a reduced share of small avian items in the prey pool of females, due to the females catching game birds of medium or large size, birds wounded by lead bullets (pheasants, ducks), or birds having swallowed such bullets by mistake (Mateo, 2009).…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, Kenntner et al (2003) did not observe such intersex relationships concerning mercury renal concentrations for German Goshawks, even though they recorded higher lead concentrations in the kidneys of females in comparison to males. That result may indicate a reduced share of small avian items in the prey pool of females, due to the females catching game birds of medium or large size, birds wounded by lead bullets (pheasants, ducks), or birds having swallowed such bullets by mistake (Mateo, 2009).…”
Section: Discussionmentioning
confidence: 60%
“…The levels of PCBs in muscle of white-breasted waterhen (3,400-1,400,000 ng/g lw) and common snipe (8,800-36,000 ng/g lw) were higher than that in eggs of little egret (863±605 ng/g lw) and blackcrowned night heron (784 ± 484 ng/g lw) found in Xiamen, South China (Lam et al 2008). Moreover, levels of PCBs in the liver of Chinese-pond heron (6,600-340,000 ng/g lw) were compared with those in the liver of predatory birds collected in Belgium (3,900-990,000 ng/g lw) and Northern goshawks (58-78,400 ng/g ww) from Germany (Kenntner et al 2003), and were higher than those in liver of birds habited in Greece (1.01-7,420 ng/g ww) (Hela et al 2006), Spain (31-19,370 ng/g ww) (van Drooge et al 2008), and South Indian (<20-1,400 ng/g ww) (Tanabe et al 1998), but were lower than that in the liver of resident birds in Japan (1,600-83,000 ng/g lw), an industrial country which had been heavily polluted by PCBs (Kunisue et al 2003).…”
Section: Occurrence and Levelsmentioning
confidence: 99%
“…Intraspecific differences in levels of bioaccumulation are generally associated with spatial or temporal variation of contaminants in the environment (Newton et al 1993;García-Fernández et al 1997;Kenntner et al 2003;Odsjö et al 2004). However, several studies have shown that for top predators diet composition can also influence the concentration of contaminants (Lindberg and Odsjö 1983;Elliot et al 1996;Anthony et al 1999;Mañosa et al 2003;Palma et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Birds are considered to be sensitive biomonitors of environmental contaminants. This is particularly the case for birds of prey because they: (1) occupy high trophic levels; (2) are longlived; and (3) many are resident and territorial, indicating local levels of environmental contamination (Becker 2003;Kenntner et al 2003).…”
Section: Introductionmentioning
confidence: 99%